PENTINGNYA PEMAHAMAN AWAK KAPAL MENGENAI ANNEX I MARPOL 1973/1978 DAN LATIHAN PENCEGAHAN PENCEMARAN MINYAK TERHADAP PENANGGULANGAN PENCEMARAN MINYAK DARI KAPAL - Kuncowati - (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2018)
One of the sources of oil pollotion at sea is from ships. This could happen because of ship accidents, tanker ship loading and discharge activities, tanks cleaning and from the ship machinery waste. Crews ship play an important role in preventing and countermeasure oil pollution at sea. International Maritime Organization (IMO) mandated that in education and training seafarers are given material on environmental awareness and pollution prevention at sea. This is meant that seafarers are understood the provisions contained in Marine Pollution (MARPOL) 1973/1978. However, sewage from the engine room and oil tanks or fuel sewage are found from the nearest land that does not meet the provisions in Marpol 1973/1978 Annex I which is very dangerous for marine ecosystems and human. This research was using questionnaire and the respondent was crews ships. This research was using quantitative analysis methods such as multiple linear regression analysis, t test, F test and determination test to know the importance of the crew ship understanding on MARPOL 1973/1978 Annex I and oil pollution prevention drills due to countermeasure oil pollution at sea . Prevention of pollution at the sea also cannot be separated from the monitor and the responsibilities of the government and related parties.Keywords : MARPOL 1973/1978, Annex I, Oil Pollution at Sea, CrewSalah satu sumber pencemaran minyak di laut adalah kapal,hal itu terjadi karena kecelakaan kapal, kegiatan bongkar muat kapal tanker,pembersihan tanki (tank cleaning) maupun dari limbah ruang permesinan kapal.Awak kapal sangat memegang peranan penting dalam mencegah dan menanggulangi pencemaran minyak di laut,. IMO (International Maritime Organisation) dalam diklat pendidikan dan latihan, pelaut diberikan materi mengenai kepedulian lingkungan dan pencegahan polusi di laut oleh kapal ,untuk mengetahui dan memahami ketentuan – ketentuan yang terdapat dalam Marine Polution (MARPOL) 1973/1978 akan tetapi masih dijumpai kapal yang membuang air got dari ruang mesin maupun air bekas mencuci tanki minyak ataupun bahan bakar dengan kandungan minyak dan jarak pembuangan dari daratan terdekat yang tidak memenuhi ketentuan dalam annex I Marpol 1973/1978, hal ini sangat berbahaya bagi ekosistem laut dan manusia.Dengan menyebar angket quitioner kepada responden yaitu awak kapal dengan metode analisisis kuantitatif yaitu analisis regresi linier berganda ,Uji t, Uji F dan uji determinasi dapat diketahui pentingnya pemahamanan awak kapal mengenai annex I MARPOL 1973/1978 dan latihan pencegahan pencemaran minyak terhadap penanggulangan pencemaran minyak di laut.Selain itu penanggulangan pencemaran minyak di laut juga tidak lepas dari monitor serta tanggung jawab pemerintahan dan pihak yang terkait.Kata kunci : Pencemaran Minyak di Laut, Awak Kapal, MARPOL